2013
DOI: 10.1093/humupd/dmt040
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of galectin-1 in reproduction: past, present and future

Abstract: The involvement of gal-1 in the regulation of different processes during the establishment, development and maintenance of pregnancy could be described as unique. Gal-1 has emerged as an important lectin with major functions in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
17

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 174 publications
0
76
0
17
Order By: Relevance
“…Integrins appear to play important roles during pregnancy through their involvement in cell invasion, migration and EMT [27]. Previous studies revealed that extracellular Gal-1 secreted by CAFs enhanced the invasiveness of GC cells by upregulating the expression of β1 integrin [22].…”
Section: Resultsmentioning
confidence: 99%
“…Integrins appear to play important roles during pregnancy through their involvement in cell invasion, migration and EMT [27]. Previous studies revealed that extracellular Gal-1 secreted by CAFs enhanced the invasiveness of GC cells by upregulating the expression of β1 integrin [22].…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse, Yakushina et al, 2015 66 shown that galectin-1 stimulates the differentiation of CD4+ cells into T-regulatory cells then being one of the key molecules involved in immune-tolerance. Probably as the result of the above, low expression in the endometrium has been associated to an increased frequency of early pregnancy failures and miscarriages 67,68 .…”
Section: Molecular Biosystems Accepted Manuscriptmentioning
confidence: 99%
“…These include the proposals that the death ligand FasL, the negative costimulatory molecule PD-L1, and the tryptophan catabolizing enzyme idoleamine 2,3-dioxygenase, which are all expressed at the maternal-fetal interface would respectively kill, render inactive, or starve infiltrating effector T cells (Baban et al , 2004, Chaouat and Clark, 2001, Taglauer et al , 2009). In contrast, there is mounting evidence that the multifunctional carbohydrate-binding protein Galectin-1 may locally regulate decidual T cell behavior to promote a uterine environment supportive of pregnancy (for review see (Barrientos et al , 2013)). Consistent with this possibility, female mice deficient in Galectin-1 show higher rates of fetal loss in allogeneic but not syngeneic pregnancies (Blois et al , 2007).…”
Section: Regulationmentioning
confidence: 99%